Three-Body Forces in Configuration-Interaction Methods for Nuclear Physics - Djärv, Tor (My University, 2016)
In this thesis, three-body forces are studied and implemented in a quantum manybody configuration-interaction method. The general importance of three-body forces in physics is discussed, providing some classical examples, before focusing in particular on their appearance in modern nuclear physics. The theoretical formalism that is needed for the implementation of three-body forces in quantum many-body systems is presented, with the angular-momentum coupling of two- and three-body systems of identical particles as main focus point. The resulting software, that is written in C, is then utilized to compute the ground-state energy of the tritium (3H) and helion (3He) nuclei in finite model spaces (Nmax 8). Results are compared with other simulations and the difference is within an acceptable tolerance. A few suggestions for future optimization of the code, such as the utilization of hash maps, are discussed.
Keywords: Annan teknik; Grundläggande vetenskaper; Hållbar utveckling; Teknisk fysik; Innovation och entreprenörskap (nyttiggörande); Materialvetenskap; Other Engineering and Technologies; Basic Sciences; Sustainable Development; Engineering physics; Innovation & Entrepreneurship; Materials Science